A One Year Epidemiological Study of Mechanical Injury Cases brought to SIMS Hospital, Western Uttar Pradesh - Abhishek Sharma, Sumit Tellewar, Barkha Gupta, Vishwajeet Singh, Gurdeep Singh (Institute of Medico-legal Publications Pvt Ltd, 2020)
Aim: To find out causes and factors responsible for the mechanical injuries. Materials & Methodology: This prospective study was conducted at Saraswathi Institute of Medical Sciences, Hapur, from 1st JULY 2017 to 30th JUNE 2018. There were total 306 patients of mechanical injury cases reported to the department of emergency during the study period. Result: Of the total 306 cases 228 (74.51%) cases were male and 78 (25.49%) cases were female. Most susceptible age group was between 21-30 years (30.1%) of age and RTA were the leading cause of death (83.66%).